PEMANFAATAN TEKNOLOGI DIGITAL UNTUK PEMBERDAYAAN UMKM DESA KAPUTIHAN - Yani Sri Mulyani; Yanti Apriyani; Miftah Farid Adiwisastra; Atyla Azfa Al Harits; Fauziah Nur Madinah (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
The use of digital technology for the empowerment of MSMEs can encourage the improvement of competitiveness and market access for business actors. In Kaputihan Village, Jatiwaras District, Tasikmalaya Regency, which has natural products and snack food production, technology has not yet been utilised as a medium to market the produced products. This community service activity is expected to help the community optimise online product marketing, increasing sales and reaching a wider market. The method used in this activity is a workshop training on the Pasar Kaputihan application for the community of MSME actors and village officials as application administrators. With the digital marketing training "Pasar Kaputihan," it is hoped that MSME actors in Kaputihan Village can understand and apply technology in their product marketing processes, thereby expanding their market, increasing sales, and enhancing the competitiveness of their products in the global market. The goal of the E-commerce application for UMKM in Kaputihan Village is to empower the residents' businesses by utilising digital technology so that the wider community can access them. In addition, this application aims to increase visibility to promote products such as handicrafts, traditional foods, or agricultural products from the village. With the presence of this application, it can create innovation and collaboration between the community and the village government, allowing the community to improve their quality of life and the income of Kaputihan village